Tezaver slovenskega ljudskega jezika na Koroškem – dokaz živosti graške slavistike - Karničar, Ludvik (Slavia Centralis, 2020)
The Thesaurus of Slovene Dialects in Carinthia – an Indication of the Vitality of Slavic Studies in Graz The article deals with the long-term dialectological project of creating a lexical inventory of the Slovene Volkssprache in Carinthia and presents some results of this project: the work on the Thesaurus (as of 2009 six volumes from A to K have been published; the seventh volume, L–M, is currently in preparation) and the lexical cartography illustrating the spread of selected diatopic synonyms in Austrian Carinthia.